Case report of gastric syphilis in Korea: Clinical features, pathology, management, and prognosis. Issue 50 (17th December 2021) - Yu, Hyung-Joo; Kim, Seong-Jung; Oh, Hyung-Hoon; Im, Chan-Mook; Han, Bora; Myung, Eun; Yun, Sook-Jung; Lee, Kyung-Hwa; Joo, Young-Eun
Abstract: Rationale: Syphilis is a contagious infectious disease caused by Treponema pallidum . Gastric involvement of syphilis is rare and has nonspecific gastrointestinal symptoms and endoscopic findings. To date, 16 cases have been reported in Korea. Here, we report 2 additional cases of gastric syphilis in men in their 30 second. Patients concerns: Two 35- and 33-year-old men presented with epigastric pain. Diagnosis: The serum venereal disease research laboratory and fluorescent treponemal antibody absorption tests were positive. Esophagogastroduodenoscopy showed multiple variable-sized flat elevated lesions and geographic ulcers with whitish exudates in the antrum and body. Warthin–Starry silver staining of endoscopic biopsy specimens confirmed gastric syphilis. Interventions: The patients were treated with an intramuscular injection of 2.4 million units of benzathine penicillin once a week for 3 weeks. Outcomes: Clinical symptoms and gastric lesions were completely resolved. Lessons: First, gastric syphilis, despite its rarity and nonspecific symptoms and endoscopic findings, should be considered in a rare extracutaneous presentation of syphilis. Second, a high index of clinical suspicion and an accurate diagnosis based on a combination of clinical, radiological, endoscopic, serologic, and histopathologic findings provide an opportunity to identify and treat patients with gastric syphilis.